2020
DOI: 10.7554/elife.48730
|View full text |Cite
|
Sign up to set email alerts
|

Circuits that encode and guide alcohol-associated preference

Abstract: A powerful feature of adaptive memory is its inherent flexibility. Alcohol and other addictive substances can remold neural circuits important for memory to reduce this flexibility. However, the mechanism through which pertinent circuits are selected and shaped remains unclear. We show that circuits required for alcohol-associated preference shift from population level dopaminergic activation to select dopamine neurons that predict behavioral choice in Drosophila melanogaster. During memory expression, subsets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 101 publications
0
46
0
1
Order By: Relevance
“…mine induce dopamine release in the fly brain 21,38,[45][46][47] . Therefore, we tested the role of dopamine receptors in the preference for ethanol and methamphetamine by using mutants of the four dopamine receptors: Dop1R1, Dop1R2, Dop2R and DopEcR.…”
Section: Dop1r1 Signaling In the Mushroom Body Regulates Drug Preferementioning
confidence: 99%
See 2 more Smart Citations
“…mine induce dopamine release in the fly brain 21,38,[45][46][47] . Therefore, we tested the role of dopamine receptors in the preference for ethanol and methamphetamine by using mutants of the four dopamine receptors: Dop1R1, Dop1R2, Dop2R and DopEcR.…”
Section: Dop1r1 Signaling In the Mushroom Body Regulates Drug Preferementioning
confidence: 99%
“…4a,d), suggesting its role in the drug aversion. Because sugar and ethanol reward is conveyed to the mushroom body (MB) in the context of associative learning 33,38,48,49 , we next tested the role of Dop1R1 in the MB. Genetic knock-down of Dop1R1 in the MB showed a consistent phenotype to the mutant, highlighting the importance of the MB in this behavior ( Fig.…”
Section: Dop1r1 Signaling In the Mushroom Body Regulates Drug Preferementioning
confidence: 99%
See 1 more Smart Citation
“…The insect central complex is an evolutionarily conserved central brain region whose ellipsoid body and protocerebral bridge sub-regions have been implicated in navigation [25][26][27][28][29][30][31][32] and sleep [33][34][35] . The central complex fan-shaped body, a laminar neural sub-region, has been implicated in sleep [36][37][38][39] and ethanol preference 40,41 . The fanshaped body was particularly interesting to us because several neuromodulators 42 , their receptors 37,43,44 , as well as dopaminergic inputs 45,46 co-localize in its layers.…”
Section: A Decision Making Neuronal Ensemble Converges On the Fan-shamentioning
confidence: 99%
“…In rodents, Rac1 in the dorsal versus ventral striatum plays opposite roles in cocaine-induced reward and spine maturation [214,215]. Furthermore, Scaplen et al recently showed that population-level dopaminergic activation encodes alcohol rewards, whereas specific microcircuits encode cued activation of alcohol memories [216]. Ideally, mechanistic studies will employ fly genetic tools and increasing insight provided by the completed fly connectome [217] to parse out the specific cell populations or circuits in which genes play a given role.…”
Section: Future Directionsmentioning
confidence: 99%